METHODOLOGY FOR DESIGNING AN INTEGRATED TECHNOLOGICAL PROCESS FOR CNC PART MANUFACTURING - Torgonov, Sh.; Botirov, A. (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article describes a new approach to designing technological processes for machining parts on metal-cutting machines under production conditions. This approach has been developed based on the preliminary prediction of machining accuracy. The process of selecting machining stage parameters is integrated with the modeling of cutting tools and technological fixture parameters. The sequence of technological process design begins with the initial operation and serves to consistently form the subsequent machining stages.